TATA KELOLA LEMBAGA PERKREDITAN DESA DALAM PENEGAKAN INTEGRITAS PADA MASYARAKAT DESA ADAT (STUDI KASUS LPD PECATU, BADUNG) - Pinatih, I Putu Indra Klinsmanata; Noak, Piers Andreas; Erviantono, Tedi (Jurnal Nawala Politika, 2023)
Village Credit Institutions (LPD) are one of the political and economic products of empowering local communities who are members of indigenous peoples. LPD politics has two uniqueness, namely ownership and decision-making processes. Catur Purusha Artha as a showcase of cultural values can be used as a basis for LPD business activities. Culture or local wisdom Catur Purusha Artha explains four things that are important for LPDs in managing business risk. In accordance with Regional Regulation No. 4 of 2019 concerning Traditional Villages, which has a philosophy of Tri Hita Karana (THK) in life, the LPD itself as a business entity owned by a Traditional Village adopts this philosophy in its operations. Likewise, the Perarem states that LPD does not only operate in the economic or socio-economic sphere, but has another mission, namely to preserve Balinese customs and culture and the environment based on THK teachings so as to produce a holistic form of accountability that is comprehensive in all aspects of life, both physical and non-physical. Based on the existing phenomena, researchers are interested and important in researching sustainable business practices and accountability carried out by LPDs based on THK.